Civil Disputes Between Government and Individuals: A Comparative Study of Indonesia and French Legal System - Wigati Pujiningrum; Rosa Agustina; Harsanto Nursadi (Unissula, 2024)
This study aims to compare the legal systems of Indonesia and France in handling civil disputes involving the government and individuals. The research highlights challenges related to judicial independence, procedural efficiency, and fair trial accessibility for private individuals in both countries. This study assesses legislative developments and procedural safeguards in both countries, examining their effectiveness in resolving disputes and identifying strengths and weaknesses. In Indonesia, the dual judiciary system separates the General Courts, which handle both civil and criminal cases, from the Administrative Courts, dedicated to disputes involving government bodies. In contrast, France’s integrated legal approach under its administrative law tradition, overseen by the Conseil d’État, emphasizes separation of powers and judicial oversight to ensure government decisions comply with the rule of law. The French system incorporates corrective justice principles, offering comprehensive remedies to address losses in civil disputes, which differ significantly from Indonesia’s approach. It underscores Indonesia’s ongoing legal reforms aimed at enhancing judicial independence and France’s robust administrative jurisprudence that checks executive power, offering insights to improve administrative justice and protect individual rights in various legal contexts.